Writing research papers : - Lester, James D (Scott, Foresman, 1971)
This market-leading text provides readers with step-by-step guidance through the research writing process, from selecting and narrowing a topic to formatting the finished document. Writing Research Papers backs up its instruction with the most complete array of samples of any writing guide of this nature.